LEGAL CERTAINTY ON THE CANCELLATION OF THE EXTENSION OF BUILDING USE RIGHTS OVER MANAGEMENT RIGHTS (STUDY OF SUPREME COURT DECISION NUMBER 245 K/TUN/2024) - Lutfia Haneda Zahara; Jamal Wiwoho; Andina Elok Puri Maharani (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the validity of the administrative action of canceling the extension of Building Use Rights (HGB) over Management Rights (HPL) by land officials and examine whether the legal considerations of the Panel of Judges in Supreme Court Decision Number 245 K/TUN/2024 have provided legal certainty for HGB holders. This problem arises due to the cancellation of the HGB extension which gives rise to disputes regarding the limits of the authority of land officials and legal protection for land rights holders. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach. The legal materials used consist of primary legal materials and secondary legal materials which are analyzed qualitatively using a prescriptive method. The results of the study indicate that the validity of the cancellation of the HGB extension must be tested based on aspects of authority, procedure, and substance in accordance with the provisions of government administrative law and applicable land regulations. In addition, the legal considerations of the Panel of Judges in Supreme Court Decision Number 245 K/TUN2024 have an important role in realizing legal certainty through testing the legality of the actions of land officials. The ruling affirms that the exercise of administrative authority must be based on statutory regulations, the principle of legal certainty, and general principles of good governance, so that the rights of HGB holders acting in good faith remain legally protected. Therefore, legal certainty in the land sector can only be achieved if every administrative action is carried out legally, proportionally, and accountably.